Evolution of global scientific collaboration in mRNA vaccine research: Insights from bibliometric and social network analysis (2010~2023) - Juan Chen; Lizi Pan; Yan Lu; Ting Zhang; Dongzi Xu; Shu Yan; Zhaolian Ouyang (Taylor & Francis Group, 2023)
ABSTRACTThe field of mRNA vaccines has witnessed rapid development in recent years, leading to significant changes in global scientific collaboration. In this study, a bibliometric and social network analysis was conducted to reveal the evolution of global scientific collaboration in mRNA vaccine research. Altogether 6974 articles published since 2010 were retrieved and categorized into Period 1 (2010-2019), Period 2 (2020-2021) and Period 3 (2022-2023). During Period 2 and 3, there was a significant rise in the proportion of publications involving domestic inter-institutional cooperation (42.0%, 54.0% and 59.1%, respectively in Period 1, 2, and 3), while a significant decrease in international cooperation (32.1%, 23.7% and 21.0%). More countries participated in international collaboration during Period 2 and 3, with the US, the UK and Germany remaining top three throughout all periods, while some other countries like Italy, Japan, and China experiencing significant shifts. Significant correlations between collaboration type and publication impact and between geographical distance and collaborative publication counts were detected. Furthermore, significant changes in research focuses and institutions that are major contributors in the mRNA vaccine development have been observed. In conclusion, the mRNA vaccine field has experienced rapid development over the past decade, with significant evolutions of global scientific collaboration detected in our study.